2021
DOI: 10.1038/s41598-021-89209-0
|View full text |Cite
|
Sign up to set email alerts
|

Inspection of the lens thickness with preoperative biometric measurements prevents an erroneous interpretation of posterior capsule during FLACS

Abstract: Optical opacity reduces quality of biometry images, making it potentially difficult to find the correct location for irradiation during femtosecond laser-assisted cataract surgery (FLACS). After experiencing a case of posterior capsule (PC) rupture because of optical opacity, we started lens thickness (LT) inspection, which indicates comparison of between intra- and pre-operatively measured LT. We retrospectively investigated the effectiveness of the LT inspection. One observer reviewed all FLACS treatment sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In their study, Kurosawa et al reported a case of posterior capsule dehiscence induced by misdirected laser irradiation, caused by the detection of a high OCT intensity area in the anterior vitreous (misinterpreted as the posterior capsule) [14]. They consequently proposed a method to avoid this complication, called LT inspection: it stands for comparing pre-operative LT (detected with IOL Master 700 and CASIA2, TOMEY) with intraoperative LT (detected with Catalys' i-OCT) before laser irradiation and, eventually, to manually correct intraoperative data based on this comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, Kurosawa et al reported a case of posterior capsule dehiscence induced by misdirected laser irradiation, caused by the detection of a high OCT intensity area in the anterior vitreous (misinterpreted as the posterior capsule) [14]. They consequently proposed a method to avoid this complication, called LT inspection: it stands for comparing pre-operative LT (detected with IOL Master 700 and CASIA2, TOMEY) with intraoperative LT (detected with Catalys' i-OCT) before laser irradiation and, eventually, to manually correct intraoperative data based on this comparison.…”
Section: Resultsmentioning
confidence: 99%
“…During FLACS, precise detection of radiation sites is critical to correct the direction of spots and to avoid complications. Kurosawa et al demonstrated that LT inspection could guide the surgeon in adjusting laser settings and avoiding posterior capsule breaks [14].…”
Section: Discussionmentioning
confidence: 99%